2006
DOI: 10.3233/nre-2006-21106
|View full text |Cite
|
Sign up to set email alerts
|

Improved fatigue in individuals with multiple sclerosis after participating in a short-term self-care programme

Abstract: Background: Fatigue is among the most common, yet least understood symptoms of Multiple Sclerosis (MS). The debilitating symptoms of MS can have adverse effects on the sufferer's self-esteem. We report the effect of a short-term self-managed graded exercise programme on fatigue and self-esteem of patients with MS. Methods: Thirty-four (age range: 20-50, mean: 29.7 years; M:F 0.7:1.0) patients with MS who lived in Tehran and were not physically disabled entered the study. Self-esteem score was measured with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 17 publications
1
7
0
Order By: Relevance
“…We compute effect sizes expressed as Cohen's d [20] in one of two ways: (a) mean change from before to after the intervention of exercise training group minus mean change of control group divided by pre-intervention pooled standard deviation (experimental trials) or (b) mean change from before to after the intervention of exercise group divided by pre-intervention standard deviation (non-experimental trials). Within the experimental trials, the effect sizes were always generated such 1 Medical Outcomes Study Short Form-12 [25] 1 Multidimensional Fatigue Inventory [8] 1 Multiple Sclerosis Impact Scale-29 [26] 1 Satisfaction With Life Scale [25] 1 Sickness Impact Profile [24] 1 Visual Analogue Fatigue Scale [27] 1…”
Section: Methodsmentioning
confidence: 99%
“…We compute effect sizes expressed as Cohen's d [20] in one of two ways: (a) mean change from before to after the intervention of exercise training group minus mean change of control group divided by pre-intervention pooled standard deviation (experimental trials) or (b) mean change from before to after the intervention of exercise group divided by pre-intervention standard deviation (non-experimental trials). Within the experimental trials, the effect sizes were always generated such 1 Medical Outcomes Study Short Form-12 [25] 1 Multidimensional Fatigue Inventory [8] 1 Multiple Sclerosis Impact Scale-29 [26] 1 Satisfaction With Life Scale [25] 1 Sickness Impact Profile [24] 1 Visual Analogue Fatigue Scale [27] 1…”
Section: Methodsmentioning
confidence: 99%
“…Recent studies provide significant evidence about the health advantages brought by self-management in people with MS [ 6 , 7 ]. It is associated with a reduction of fatigue [ 8 ], improvement in health-related quality of life [ 9 ], adherence to medication [ 10 ], and increase in physical functioning [ 11 , 12 ]. In the systematic review of Rae-Grant et al [ 13 ], treatment outcomes in MS were shown to improve with the efficacy of self-management.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10][11][12] However, relatively little published evidence about MS care management programs is available. Some earlier studies have shown the feasibility of programs for patient education, exercise, specialist nurse, depression disease management, and energy conservation among people with MS. [13][14][15][16][17] Most of these studies were symptom specific and few were conducted on a wide scale. There is a need to understand the impact of this type of program and facilitate informed decision-making for review and implementation.…”
Section: Introductionmentioning
confidence: 99%